Integrating TOE, TAM, and UTAUT to Analyze E-Bidding Effectiveness in Vietnam - Nguyen, Quoc Toan; Nguyen, Thi Thu Hien; Tran, Trung Kien (International Journal of Sustainable Construction Engineering and Technology, 2025)
This study develops an integrated conceptual framework to assess the effectiveness of electronic construction tendering (ECT) in Vietnam’s public procurement sector. Although ECT is legally mandated, implementation remains uneven, particularly among small and medium-sized enterprises (SMEs). To analyze this complexity, the framework combines three established models - Technology-Organization-Environment (TOE), Technology Acceptance Model (TAM), and Unified Theory of Acceptance and Use of Technology (UTAUT) - capturing key dimensions such as infrastructure readiness, organizational capacity, institutional environment, and user behavior. Notably, the study redefines “attitude toward technology” as an organization’s adaptive capacity, rather than individual intention, to reflect Vietnam’s semi-coercive digital transition. The proposed model lays the groundwork for empirical testing and offers concrete policy directions, including subsidized training and mobile-based access for rural SMEs, integration incentives for larger firms, and legal reforms to stabilize the regulatory environment. These insights aim to inform more effective and inclusive digital transformation strategies in the construction sector.